SKRINING FITOKIMIA DAN UJI TOKSISITAS EKSTRAK KASAR, FRAKSI N-HEKSANA, ETIL ASETAT, DAN METANOL-AIR DAUN KIRINYUH (Chromolaena odorata (L.) King & H.E Robins) - Tri Riski Amalia; Djihan Ryn Pratiwi; Erwin Erwin (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2022)
Kirinyuh leaves (Chromolaena odorata (L.) King & H.E Robins) is one of the plants of the Asteraceae family that is commonly used by the community as a wound healing medicinal ingredient and has antioxidant and antibacterial activities. This research was conducted to determine the type of secondary metabolite compounds contained in the crude extract, n-Hexane, ethyl acetate and methanol-water fraction kirinyuh leaves (Chromolaena odorata (L.) King & H.E Robins) and determine the level of toxicity against to Artemia salina L. using the BSLT method. Phytochemical test results of crude extract leaves kirinyuh (Chromolaena odorata (L.) King & H.E Robins) contain alkaloids, flavonoids, steroids, and phenolics. The n-Hexane fraction contains steroids and quinones. The ethyl acetate fraction contains flavonoids and phenolics. The methanol-water fraction contains flavonoids, saponins and phenolics. Based on toxicity tests, crude extract, n-hexane, ethyl acetate fractions of kirinyuh leaves is highly toxic with successive LC50 values of 2.88 ppm, 8.12 ppm and 6.86 ppm, then the methanol-water fraction is toxic with an LC50 value of 186.76 ppm. Keywords: Kirinyuh leaves, phytochemicals, toxicity